The reality of Media Education in Public educational institution in the kingdom of Saudi Arabia: Jeddah as an example (Journal of Educational and Psychological Sciences, 2019)
The problem of the study manifested in the following main question: What is the reality of media education in public education institutions in the Kingdom of Saudi Arabia? In order to answer this question, the study aimed to reveal the topics of media education in the school curricula and to reveal their practices in the educational departments in Jeddah governorate, to diagnose the reality of media education in the public education institutions from the point of view of the teachers in Jeddah governorate in terms of (its concept, importance, activities, skills and obstacles), The study also used the descriptive (analytical) method. The study resulted in a series of results, the most prominent of which are: the school curriculum provides various topics for media education based on the integration approach in all educational stages. The Department of Education adopts a range of activities and courses that enable students and teachers to deal positively with the media, The field study showed that the concept of media education is available in 63% in the sample of the study in a medium degree, also 64% believe that the reasons for interest in media education are medium degree, 56% see That media literacy skills are sometimes given to students at school, and 73% agree that obstacles often impede the application of media education in school.